2016
DOI: 10.1007/s40415-016-0326-3
|View full text |Cite
|
Sign up to set email alerts
|

Fungi, algae, and other palynomorphs in sedimentary profiles collected from two forests in the northernmost coastal plain from Rio Grande do Sul, southern Brazil

Abstract: Fungi, algae, and other palynomorphs in sedimentary profiles collected from two forests in the northernmost coastal plain from Rio Grande do Sul, southern Brazil). We present, for the first time, taxonomic descriptions of 13 fungi, eight algae, three acritarchs, and nine other palynomorphs preserved in two Quaternary sediment profiles: Pirataba forest site (29°15 0 S-49°51 0 W) and Faxinal forest site (29°21 0 S-49°45 0 W), Torres Municipality, northernmost coastal plain from Rio Grande do Sul, southern Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In this present study, we showed, for the first time, a catalog of angiosperm pollen preserved in two Quaternary sediment profiles from the extreme northern coastal plain of Rio Grande do Sul, in the Faxinal and Pirataba rain forests of Torres Municipality. This is a continuation of our previous work on bryophyte and pteridophyte spores and gymnosperm pollen grains (Roth and Lorscheitter 2013), fungi, algae, and other palynomorphs (Roth and Lorscheitter 2016).…”
Section: Introductionsupporting
confidence: 75%
“…In this present study, we showed, for the first time, a catalog of angiosperm pollen preserved in two Quaternary sediment profiles from the extreme northern coastal plain of Rio Grande do Sul, in the Faxinal and Pirataba rain forests of Torres Municipality. This is a continuation of our previous work on bryophyte and pteridophyte spores and gymnosperm pollen grains (Roth and Lorscheitter 2013), fungi, algae, and other palynomorphs (Roth and Lorscheitter 2016).…”
Section: Introductionsupporting
confidence: 75%
“…Reference catalogs on many taxa of palynomorphs preserved in Quaternary sediments, related to other portions of the expansive RS coastal plain, have already been produced (Lorscheitter 1988(Lorscheitter , 1989Cordeiro 1991;Neves & Lorscheitter 1992, 1995bNeves & Bauermann 2004;Neves & Cancelli 2006;Macedo et al 2009;Roth & Lorscheitter 2013;Masetto & Lorscheitter 2014Roth & Lorscheitter 2016. Future cataloging efforts should continue to the coastal plain, with descriptions and illustrations of palynomorphs and ecological data of the source organism, i.e., the basic reference material for paleoenvironmental analyses.…”
Section: Discussionmentioning
confidence: 99%
“…2, figs 5 and 6;Aggarwal et al 2015: figs 2-4) are mostly interpreted as remains of fungi and compared to modern pollen-colonizing Chytridiomycota. On the other hand, Mesozoic and Cenozoic non-pollen palynomorph (NPP) assemblages frequently contain spores of microthyriaceous and other fungi that are morphologically similar to the spores produced by certain present-day fungal parasites and pathogens(e.g., Höhnel 1924; Van Geel and Anderson 1988;Kalgutkar and Jansonius 2000;Van Geel 2002;Singh and Tripathi 2010;Kürschner et al 2015;Schumilovskikh et al 2015;Roth and Lorscheitter 2016).…”
mentioning
confidence: 99%